Promoting pre-class guidance and in-class reflection: A SQIRC-based mobile flipped learning approach to promoting students' billiards skills, strategies, motivation and self-efficacy. (January 2021) - Lin, Yen-Nan; Hsia, Lu-Ho; Hwang, Gwo-Jen
Abstract: In order to facilitate students' learning performance and ability of knowledge application, flipped learning has been integrated into various disciplines so as to increase students' opportunities to practice and solve their learning difficulties under the teacher's guidance. Nonetheless, previous flipped studies focused more on students' performances in terms of cognition, while courses aimed at training students' skills and strategies have generally been ignored. To address this issue, the present study proposes the "Scaffolding, Questioning, Interflow, Reflection and Comparison" (SQIRC-based mobile flipped learning) approach to strengthen pre-class guidance and in-class reflection by referring to the theories of cognitive apprenticeship and reflective practice. To examine the effects of the SQIRC-based learning approach, the current study adopted a quasi-experiment in the billiards course at a university. A total of 35 students were recruited as the experimental group who adopted the SQIRC-based mobile flipped learning approach, while 40 students in the control group adopted the conventional mobile flipped learning approach. The findings indicated that the SQIRC-based mobile flipped learning significantly improved the students' performance on billiards striking strategies, self-efficacy, and learning motivation. It is verified that the design of video-recording activities with reflection and comparison guidance is the key to promoting students' billiards strategies and skills in flipped learning, which can effectively stimulate students' self-reflection, and promote the improvement of sports performance, self-efficacy and intrinsic motivation. At the same time, it fully presents the design of teaching activities before and during class, and contributes to theory and teaching practice. In addition, discussion of the findings, limitations of the present study, and suggestions for generalizing the proposed approach to other application domains are provided. Highlights: A mobile flipped learning approach for billiards is proposed. The approach is proposed based on cognitive apprenticeship. The approach improved students' performance on billiards striking and strategies. The approach improved students' self-efficacy and learning motivation. The approach had positive effects on students' in-class learning engagement.